Teachers' Perceptions of the Physics Learning Process Using the Direct Instruction Model in Junior High Schools - Yani, Resky; Ismail, Ismail; Poh, Sing Huat (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to identify teachers' perceptions of the physics learning process using the direct instruction model at senior high school 1 Jeneponto. Methodology: This research is a qualitative research that produces data presented in narrative form and describes what is from a variable, symptom or condition and does not intend to test the hypothesis. The data sources in this study were three physics teachers at senior high school 1 Jeneponto. Main Findings: The results of the study showed that students and physics teachers of senior high school 1 Jeneponto have a positive perception of the Direct Instruction learning model. Teachers apply the Direct Instruction learning model according to the steps in the theory, while some teachers do not implement the steps of the direct instruction learning model in the practical section because there are no practical tools for class XII material, teachers have prepared the things needed in learning, teachers have the ability to teach according to the existing theory. By using this direct instruction learning model, students have been able to achieve several achievements and have played an active role in learning. Novelty/Originality of this study: The novelty of this study lies in revealing physics teachers' contextual perceptions of the Direct Instruction model through a qualitative approach. Despite limited practical tools, teachers strive to follow the model, positively impacting student engagement and achievement. This offers a fresh perspective on its real-world implementation rarely explored in prior studies.